2017
DOI: 10.1002/2016ja023829
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal modulation of electron and mass densities at middle and auroral latitudes: Effect of geomagnetic field strength

Abstract: In this study, the effect of a reduction in magnetic field strength on the longitudinal modulation of electron density (ΔNe) and mass density (Δρ) is investigated. We study conditions during the September equinox and June and December solstices at middle and auroral latitudes in both Northern and Southern Hemispheres. The Global Ionosphere‐Thermosphere Model was employed for the theoretical study. Simulations were performed with a realistic International Geomagnetic Reference Field (IGRF) model and an IGRF mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Both the simulation and observation show pretty similar solar cycle variations with time. In addition, both the simulation and observation also show long term trend variation independent of solar activity, which is a hot topic recently in the community (Laštovička et al, 2006; Yue et al, 2008; Wang et al, 2017). The model overestimates the h m F 2 especially over solar minimum (e.g.…”
Section: The Path To Probe Space Environment Evolutionmentioning
confidence: 83%
“…Both the simulation and observation show pretty similar solar cycle variations with time. In addition, both the simulation and observation also show long term trend variation independent of solar activity, which is a hot topic recently in the community (Laštovička et al, 2006; Yue et al, 2008; Wang et al, 2017). The model overestimates the h m F 2 especially over solar minimum (e.g.…”
Section: The Path To Probe Space Environment Evolutionmentioning
confidence: 83%
“…Accordingly, a general understanding of the asymmetric features of the auroral and subauroral V z in the GEO coordinates can help us to obtain a more complete physical picture about the asymmetric behavior of V z at high MLATs and further comprehension of the tightly coupled ionosphere‐thermosphere system. Meanwhile, note that the relatively larger magnetic inclination in the auroral and subauroral regions can lead to stronger effects of E × B drift and larger biases between the vertical and field‐aligned velocity (Deng & Ridley, ; Wang et al, ). Thus in this section, only a preliminary study is carried out to describe the general hemispheric difference in the auroral and subauroral V z .…”
Section: Observations and Discussionmentioning
confidence: 99%
“…Inside the polar cap, which is defined as the region at MLATs poleward of 77°N/S, V z can be taken as a good proxy for the field‐aligned drift. However, it should be noted that in the auroral and subauroral regions, there is a relatively larger bias between V z and field‐aligned velocity because of the effect of the magnetic inclination and declination (Deng & Ridley, ; Wang et al, ).…”
Section: Dmsp Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Such a method of using a scaled dipole field is further used in other studies to examine the magnetosphere-ionosphere coupling and the dependences on the interplanetary magnetic field (IMF) (e.g., , Zieger, Vogt, Ridley, & Glassmeier, 2006. H. Wang et al (2017) found that reduced geomagnetic fields generally lead to an increase of the thermospheric mass density but a decrease of electron density at auroral latitudes. Some studies also investigated the effects of equatorial dipole magnetosphere (Zieger et al, 2004) or quadrupole configurations (Vogt et al, 2004(Vogt et al, , 2007 and suggested that high-energy particles in the MeV range are more likely to penetrate to about 𝐴𝐴 40 • altitude atmosphere during the reversal.…”
mentioning
confidence: 99%